Investigating Direct Speaking Strategies of Non-English-Majored Students at a University in Dong Nai Province - Nguyen Thi Loan (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2022)
English communication skills are now considered a passport-like requirement for students seeking a secure profession with a higher wage. Additionally, English proficiency is considered one of the variables affecting the success of foreign businesses investing in Vietnam and Vietnamese businesses looking to collaborate internationally to develop their brands into new markets abroad. The integration of various linguistic skills demonstrates the value of speaking. The main objective of this study was to investigate the frequency and importance of using direct speaking strategies by non-English-majored students at Dong Nai Technology University. The study involved 90 second-year undergraduate students at Dong Nai Technology University in Bien Hoa city, Dong Nai province. At the time of the study, the participants were 18-19 and had already attained elementary level. This research uses questionnaires and interviews using the SPSS application to analyze the main points relating to the research questions. According to research, direct speaking strategies significantly affect the English speaking skills of Dong Nai Technology University students. At the same time, the difficulties and orientations when learning speaking skills using direct speaking strategies were revealed in the study's conclusion. To maximize direct speaking strategies and advance the field of study, recommendations have been made for non-English-majored students.